Can Institutions or Education Explain World Poverty? An Augmented Solow Model Provides Some Insights (2004)
When the Solow model is augmented with variables for institutions and human capital and estimated with national data for rates of investment in education, it can explain most of the variation in cross-country standards of living. The empirical results indicate that human capital is as important as physical capital in the determination of national income and that a high government share of consumption substantially reduces total factor productivity (TFP) and national income. The results also indicate that government integrity is endogenous in the development process and has an uncertain effect on total factor productivity.